KINERJA PEGAWAI PADA DINAS PERTANIAN DAN PETERNAKAN PROVINSI RIAU - Nurainni "; Ernawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Performance Evaluation is important for measuring activity of employee, because it will describe how company doing activity effectively to achieve goals that had been determent. Organization’s planning will be achieved if employee does their jobs correctly, employee will do their jobs correctly if they have competency and credibility for doing that. As governance employee, they should give a best service for public society or people who need help for administration because governance employee has main jobs to serve citizen. All the governance employee’s jobs must serve citizen’s needs, help people who needs information for their business and give people with high quality service. The thesis is using concept of theory from performance evaluation theory by Hasibuan. The indicators that showing for this experiment are Achievement, Disciplinary, Creativity, Cooperation, Competency, and Responsibility. Population for this thesis are all employee that understand about how important performance evaluation and farmer who getting assistance. Key informan is General Subsidiary and Employee Department. For getting this information, researcher use Snowball Sampling technique. In analyzing data, researcher does deskriptif kualitatif methods with Triangulasi Technique. According this thesis that searching about how performance evaluation for governance employee of Agriculture and Husbandry Department, Riau Province in doing their jobs, we can take a conclusion from people responses that all the governance employee has being done their jobs correctly and effectively although a few responses said that they are still needing support to work better like improving education and discipline attitude.Key Word: Performance of Employee